Visuelle Medien im christlichen Kult Fallstudien aus dem 13. bis 16. Jahrhundert - Schwarz, Michael Viktor (2002)
The concepts of art history were developed in the nineteenth century. This can inhibit dialogue with neighbouring disciplines. The concept "medium", which belongs to the late twentieth century, can provide assistance and connect the argument of art history to the contemporary state of consciousness at least in the cultural sciences dealing with communication. At the centre of the book lie questions of the use and effect of objects. Dealing with a series of high-ranking art works, an observational method is practised that is both historically founded and compatible with modern discourses. The six case studies address the Naumburg Stifterfiguren, Pietro Lorenzetti's frescos in Assisi, the Parament of Narbonne, the tomb of Archbishop Chichele in Canterbury, Raphael's Sistine Madonna in Dresden, and the self-portraits of Anton Pilgram in St Stephen's Church in Vienna.